Total systems design for the procurement services of DPWH - Llanes, Emmalie Claire C.; Roque, Jennilyn T.; Sulit, Camille B.
The Philippines' Department of Public Works and Highways, abbreviated as DPWH, is the executive department of the Philippine government responsible for all safety of projects in the field of public works. It is also responsible for the maintenance of the maintenance of the Philippine road network and irrigation system. Being one of the three department of the government undertaking major infrastructure project, the Department of Public Works Highways (DPWH) must entail strict and tight implementation of policies and procedures to attain national development objectives without sacrificing the standard quality of public works and services. The proponent have identified have identified an existing problem in the flow of activities in the Procurement Department. Upon investigation of the projects from the Procurement Monitoring Report for July 2014 to December 2014, out of 33 completely documented projects 61% of which, equivalent to 21 projects, are proven to have been implemented at a later date than what was written in the contract. To be able to provide solutions to the problems and gaps identified, the group conducted an in-depth investigation on the main sources of delays in the procurement activities. This entailed gathering and collecting data from other bureaus and offices which Procurement Service closely work with. It must be emphasized that value for money in procurement is not only related to direct cost of the project but should also include quality of contractors, cost of contract and processing time. The possible sources of risks existing in the sphere of DPWH Procurement Activities are summarized to 5 categories namely, Implementing Office, Procurement Services (PrS), Bids and Award Committee (BAC), Contractors and Other External Factors. From the completely documented projects for July 2014 to December 2014, theres a high number of instances wherein Actual Completion of each project did not comply in the standard number of days specification in the RA 9184. Upon further investigation, it was also found out that there are a number of projects wherein Actual Project Dates significantly deviated from the Project Procurement Management Plan (PPMP). In summary, the current system lacks (1) system on adequate check of contractors and feedback on their performance and (2) comprehensive system of control over all stages of procurement process. Although there are project management schemes implemented by IO, BOC, BOD, BQS and PMO independently, there's no entity that actually weaves together all the performance assessments into a consolidated output. This is caused mainly by the mindset that the scope of work of Procurement Services, specifically Civil Works Division, is to serve as secretarial arm of the Bids and Awards Committee and to prepare all necessary documents for Procurement purposes. From the result of the analysis, the proponents have arrived with the following recommendations: (1) Create a Monitoring Section for Civil Works to ensure timeliness of procurement activities, (2) Contractor Management System to evaluate contractor performance, and lastly, (3) Department order for stronger contractor compliance through using CPES ratings AND Certificate of Completion/Acceptance for eligibility checking. SWOT (Strength, Weakness, Opportunities, and Threats) analysis tool was used to evaluate the risks and benefits incorporated for each of the alternatives. In conclusion, PrS must serve as liaison to all other external groups and must provide a consolidated output of evaluating performance concerning Procurement procedures o ensure high quality standards of Procurement service. There must be an interlink in all of the various groups and offices involved in the different activities of Procurement from start to finish. It shall be a conscious effort by PrS to ensure that contractors getting in their company are properly monitored, and well-handled. In the end, the main goal of each is to align their operations with the vision of DPWH - "Right Project, Right Cost, Right Quality, Right on Time". Instead of focusing on secretariat alone, PrS must be more empowered and enabled in providing measures to improve efficiency and effectivity of Procurement Procedures.